Living Space: The Contemporary Housing Environment as a Place for the Family - Dudzic-Gyurkovich Karolina (Technical Transactions, 2023)
This paper discusses housing areas from the perspective of meeting the living needs of families. In recent decades, significant changes have been observed in Poland both in terms of the formation of new housing complexes and in social expectations regarding living conditions. The new housing complexes differ significantly from the traditional, typical ones with distinctive architecture and low-standard common spaces, commonly referred to as panel block housing estates. Previous research on housing environment quality generally points to the need to create developments that provide the highest possible quality of life. These studies focused on the problems of one particular group of residents, such as children, seniors or people with disabilities. However, families, which make up a significant portion of the population and are important users, have not been adequately addressed in urban planning studies to date. Therefore, this problem merits investigation and existing research methods or urban development concepts that can be used to evaluate residential areas should be identified as should factors and spatio-functional characteristics of residential areas that can influence the creation of high-quality space for families. This study, based on a literature review, evaluated two selected development models in terms of providing optimal living conditions for families. It was found that current proposals may be useful in determining features of family-dedicated space, yet they display a range of deficiencies that should be addressed. The study’s conclusions can be used as a basis for further investigation and as recommendations in the context of planning and urban policymaking.